Hot Potatoesلترقية تعليم مهارة القراءة - Huda, Hisbullah; Baihaqi, Muhammad; Amrulloh, Muhammad Zakki; Khaidaroh, Hilda Fairuzia; Laela, Khoshiyatu Nur (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
The world of education is increasingly sophisticated with the presence of developed technology, one of which is to make it easier for students to learn whenever and wherever. Many applications that students can use to improve maharah qiraah one of them is the potatoes hot application. This research aims to find out how to use a hot potatoes application for increased student reading camp. This research is qualitative research. Data sources were collected from textbooks and results from questionnaires. The results of this study were to use the hot potatoes application for maharah qiroah exercise more effectively. With this application, teachers are expected to be more updated and can use technology to the maximum, to make it more interesting. In previous research, it focused on evaluation by using the hot pitatoes application, but focused on this research is the linguistic practice in maharah qiroah.